Sleep quality in patients with schizophrenia: The relevance of physical activity - Costa, Raquel (2018)
Patients with schizophrenia experience poor sleep quality that affects their physical and mental health. In the general population, physical activity (PA) is considered as a beneficial non-pharmacological intervention for sleep quality. However, there is a lack of research concerning its implications in the sleep quality of patients with schizophrenia. Therefore, the purpose of this study was to assess the associations between PA levels and sleep quality. One hundred and thirteen patients (28 women and 56 inpatients) with schizophrenia participated in the study. PA levels and sleep quality were assessed via standardized questionnaires, Short-Form International Physical Activity Questionnaire (IPAQ-SF) and Pittsburgh Sleep Quality Index (PSQI) respectively. Multiple linear regression models were conducted. Results demonstrated that sleep quality was positively associated with time of moderate and total PA per week. No associations were found between PA levels and anxiolytics and antipsychotic medication. Pearson's correlations showed that some of IPAQ-SF measures are negatively correlated with some PSQI components. More research is needed to explore the potential interaction between sleep quality and PA levels in patients with schizophrenia.